Hubungan BBLR dengan Kejadian Stunting pada Anak Usia 24-60 Bulan di Wilayah Kerja Puskesmas Tabanan I Tahun 2018-2019 - WIDHIDEWI, NI WAYAN; PRIYANKA HERMAWAN, PUTU; ELMY SANIATHI, NI KADEK (Hang Tuah Medical Journal, 2025)
Stunting is caused by a lack of nutritional intake for a long time so that it can cause disturbances in physical development and cognitive function that can cause death. One of the factors that influence the occurrence of stunting in toddlers is the history of low birth weight. This study aims to examine the relationship between low birth weight (LBW) and the incidence of stunting in children aged 24-60 months in the Tabanan I Health Center Working Area in 2018-2019 using analytical research methods and case control study designs and using secondary data collection methods derived from the nutrition sections. The study sample was a total of 190 toddlers recorded in the stunting and LBW report at Tabanan I Health Center, during 2018-2019 who met the inclusion and exclusion criteria obtained using consecutive sampling technique. Data analysis was performed univariately and bivariately using SPSS version 25.0 with the Spearman correlation test. The results of the chi square test showed that the p value was less than the significant level (p < 0.05), it can be stated that there is an association between low birth weight and the incidence of stunting in children aged 24-60 months in the Tabanan I Health Center Working Area. The result of Levene's test is 0,184 (>0.05) which means that the variance of data between stunting and normal groups is homogeneous or the same. Conclusion toddlers who suffer from LBW have a 2,17 greater risk of experiencing stunting than toddlers who do not experience LBW.